2001
DOI: 10.1021/bi010176t
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte Spectrin Is an E2 Ubiquitin Conjugating Enzyme

Abstract: The involvement of red blood cell spectrin in the ubiquitination process was studied. Spectrin was found to form two ubiquitin-associated derivatives, a DTT-sensitive ubiquitin adduct and a DTT-insensitive conjugate, characteristic intermediate and final products of the ubiquitination reaction cascade. In addition to spectrin and ubiquitin, ubiquitin-activating enzyme (E1) and ATP were necessary and sufficient to form both the spectrin-ubiquitin adduct and conjugate. No exogenous ubiquitin-conjugating (E2) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 84 publications
0
33
0
Order By: Relevance
“…Interestingly, the aV domain contains spectrin repeats 20-22 that our laboratory indicated as containing likely E2/E3 and ubiquitin acceptor sites [17]. Mature RBCs have lost their nucleus and other organelles including most proteosomes, and, therefore, ubiquitination of spectrin in the erythrocyte probably primarily serves regulatory roles in protein-protein interactions.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Interestingly, the aV domain contains spectrin repeats 20-22 that our laboratory indicated as containing likely E2/E3 and ubiquitin acceptor sites [17]. Mature RBCs have lost their nucleus and other organelles including most proteosomes, and, therefore, ubiquitination of spectrin in the erythrocyte probably primarily serves regulatory roles in protein-protein interactions.…”
Section: Discussionmentioning
confidence: 96%
“…Galluzi et al [9,10] have demonstrated two ubiquitination sites within a-spectrin: one in a-spectrin repeat 17 and the other in a-spectrin repeats 20 and 21. It has been further demonstrated by our laboratory that a 0 -spectrin represents ubiquitin attached to a-spectrin via a thioester bond, and this ubiquitin spectrin adduct has E2 ubiquitin conjugating activity and can transfer the ubiquitin (possibly via an E3 site) to an intramolecular DTT insensitive target site in a-spectrin repeats 20/21 [17].…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations